Influencing Preferences for Different Types of Causal Explanation of Complex Events. (December 2014) - Klein, Gary; Rasmussen, Louise; Lin, Mei-Hua; Hoffman, Robert R.; Case, Jason
Objective: We examined preferences for different forms of causal explanations for indeterminate situations. Background: Klein and Hoffman distinguished several forms of causal explanations for indeterminate, complex situations: single-cause explanations, lists of causes, and explanations that interrelate several causes. What governs our preferences for single-cause (simple) versus multiple-cause (complex) explanations? Method: In three experiments, we examined the effect of target audience, explanatory context, participant nationality, and explanation type. All participants were college students. Participants were given two scenarios, one regarding the U.S. economic collapse in 2007 to 2008 and the other about the sudden success of the U.S. military in Iraq in 2007. The participants were asked to assess various types of causal explanations for each of the scenarios, with reference to one or more purposes or audience for the explanations. Results: Participants preferred simple explanations for presentation to less sophisticated audiences. Malaysian students of Chinese ethnicity preferred complex explanations more than did American students. The form of presentation made a difference: Participants preferred complex to simple explanations when given a chance to compare the two, but the preference for simple explanations increased when there was no chance for comparison, and the difference between Americans and Malaysians disappeared. Conclusions: Preferences for explanation forms can vary with the context and with the audience, and they depend on the nature of the alternatives that are provided. Application: Guidance for decision-aiding technology and training systems that provide explanations need to involve consideration of the form and depth of the accounts provided as well as the intended audience.